Process Streams' Temperature Flexibility for Energy Savings in HENs - Osman, Abdelbagi (2010)
The increasing pressures from current economic uncertainties and the tighter environmental regulations have substantiated for more energy conservation projects to be reviewed and analysed properly. Retrofit of Heat Exchanger Network (HEN) is among the common projects to reduce plant operational cost. Based on the plus/minus principle of Pinch Technology, this paper is addressing a new concept of varying the process streams' temperature as a means of increasing the heat recovery for the process heat exchanger network.